INDIVIDUAL FACTORS CONTRIBUTING TO LOWER BACK PAIN AMONG MALES AGED 20 TO 35 YEARS ATTENDING THE SPINAL CLINIC AT MULAGO NATIONAL REFERRAL HOSPITAL IN KAMPALA DISTRICT. A CROSS-SECTIONAL STUDY. - Kiberu, Shafic (Student’s Journal of Health Research Africa, 2024)
Background The gradual increase in cases of Back pain among the general population has been one of the neglected health concerns in developing countries. The study aims to assess the specific individual factors contributing to lower back pain among males aged 20 to 35 years. Methodology A cross-sectional survey involving the collection of quantitative data from 190 respondents including 14 Surgeons and other doctors, 40 nursing staff, 19 Administrative and support staff, and 108 patients. Results Prolonged sitting, poor posture, workplace ergonomics, stress, sleep quality, diet, and previous injuries or medical conditions were identified as significant contributors to LBP. Extended periods of sitting lead to an increase in LBP, with a mean score of 4.30. The standard deviation of 0.396 suggests agreement in opinions regarding the influence of poor posture on LBP. A relatively high standard deviation of 1.291 suggests variability in opinions regarding the relationship between stress and lower back pain. The overall mean score for all specific individual factors analyzed is 3.78, with a standard deviation of 0.489, indicating a high level of agreement among respondents regarding the impact of these factors on LBP. Most of the staff fall within the age range of 31 to 40 years, comprising 58% of the total surveyed population followed by staff aged 40 years and above, accounting for 25%. Potential age-related factors that may influence the occurrence of LBP. 53% are male, while 48% are female. Conclusion Poor posture, workplace ergonomics, stress, sleep quality, diet, and previous injuries or medical conditions were identified as the most significant contributors to LBP. Recommendation Developing patient education and self-management programs can empower individuals with low back pain to take an active role in managing their condition and preventing recurrences.